2001
DOI: 10.1128/aem.67.4.1437-1444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Locus for Cadmium Resistance in Pseudomonas putida Consisting of a Cadmium-Transporting ATPase and a MerR Family Response Regulator

Abstract: Pseudomonads from environmental sources vary widely in their sensitivity to cadmium, but the basis for this resistance is largely uncharactarized. A chromosomal fragment encoding cadmium resistance was cloned from Pseudomonas putida 06909, a rhizosphere bacterium, and sequence analysis revealed two divergently transcribed genes, cadA and cadR. CadA was similar to cadmium-transporting ATPases known mostly from grampositive bacteria, and to ZntA, a lead-, zinc-, and cadmium-transporting ATPase from Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 59 publications
5
161
0
2
Order By: Relevance
“…Instead we detected cadA which is mostly found in Gram-positive bacteria [50][51][52][53]. The genome sequences of several Gram-negative bacteria have revealed homologs of cadA [54,55] and there are some reports of cadA-encoded cadmium resistance being identified in some Pseudomonas species [56,57]. The cadA gene detected in this study is believed to be chromosomally located since southern hybridisation did not detect the presence of the gene on the plasmids in any of the isolates tested.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Instead we detected cadA which is mostly found in Gram-positive bacteria [50][51][52][53]. The genome sequences of several Gram-negative bacteria have revealed homologs of cadA [54,55] and there are some reports of cadA-encoded cadmium resistance being identified in some Pseudomonas species [56,57]. The cadA gene detected in this study is believed to be chromosomally located since southern hybridisation did not detect the presence of the gene on the plasmids in any of the isolates tested.…”
Section: Discussionmentioning
confidence: 57%
“…The cadA gene detected in this study is believed to be chromosomally located since southern hybridisation did not detect the presence of the gene on the plasmids in any of the isolates tested. Chromosomally located cadA have also been reported in P. putida [57].…”
Section: Discussionmentioning
confidence: 89%
“…The existence of a Zn-specific sensor element is peculiar, as all of the transcription factors and resistance mechanisms known for Zn 2+ thus far cross-react with Cd 2+ and Pb 2+ (see Table 1). 17,[21][22][23][24] However, as only three sensor elements (the promoters of zntA from E. coli, cadA from P. putida and cadA from S. aureus) have been previously used for the construction of Zn/Cd/Pb-bioreporters, it is still possible that an open-minded search for new heavy-metal-regulated promoters would yield bioreporters with different specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar motifs were found in TcHMA4-C and AtHMA4-C, this domain is also the most divergent part between the two sequences. CC dipeptides were only found, together with a His-rich domain, in the N-terminal region of bacterial CPx-ATPases and were associated with Cd 2þ tolerance [28,29]. The function of these putative heavy metal binding motifs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…All these three peptides also contained three additional cysteine motifs -C(x) 4 C, C(x) 3-5 CC, CC -and a His rich domain within their extended C-terminus which could be involved in heavy metal binding. Further examination of the two putative HMA4 COOH tails revealed that the C(x) 3 CC motifs were in a larger cysteine motif, C(x) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] C(x) 3 CC for Thlaspi and C(x) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] C(x) 3 CC for Arabidopsis. This sequence is similar to the recently described TRASH domain, C(x) [19][20][21][22] C(x) 3 C, predicted to be involved in heavy metal sensing, trafficking and resistance [25].…”
Section: Isolation Of T Caerulescens Hma4 Cdnamentioning
confidence: 99%